Development of a Hovering-Type Intelligent Autonomous Underwater Vehicle, P-SURO - Li, Ji-Hong; Park, Sung-Kook; Oh, Seung-Sub; Suh, Jin-Ho; Yoon, Gyeong-Hwan; Baek, Myeong-Sook (IntechOpen, 2011)
None